IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH PREVIEW, QUESTION, READ, REFLECT, RECITE, AND REVIEW (PQ4R) - Mediana Manalu (Universitas Negeri Medan, 2014)
This study concerned on improving students’ achievement in readaing comprehension narrative text through preview, question, read, reflect, recite, and review (PQ4R) technique. This study was limited on the second year junior high school students’ achievement in reading comprehension after teaching by applying preview,question, read, reflect, recite, and review ( PQ4R).The objective of this study was to find out the improvement of students, achievement on reading comprehension through PQ4R technique.The subject of the study was VIII-1 students of SMP N 4 Pagaran. The numbers of the students were 35. The techniques for data analysis were quantitative dataand qualitative data.In analyzing the quantitative data, the mean of the students’ score for the test I cycle I was 53.62, the mean score of test II in cycle II was 73.28, the mean of test III in cycle II was 75.65. The conclusion is that PQ4R can improve the students’ achievement in reading comprehension narrative text. Keywords: Reading, Reading Test, Classroom Action Research.